2013
DOI: 10.1038/nature12679
|View full text |Cite
|
Sign up to set email alerts
|

Chasing acyl carrier protein through a catalytic cycle of lipid A production

Abstract: Summary Acyl-carrier-protein (ACP) represents one of the most highly conserved proteins across all domains of life and is nature's way of transporting hydrocarbon-chains in vivo. Notably, type II ACPs serve as a crucial interaction hub within primary cellular metabolism1 by communicating transiently between partner enzymes of the numerous biosynthetic pathways2,3. However, the highly transient nature of such interactions and the inherent conformational mobility of ACP2 have stymied previous attempts to structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
103
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(106 citation statements)
references
References 41 publications
(55 reference statements)
2
103
0
1
Order By: Relevance
“…S4D). That ACP interaction with proteins is primarily driven by electrostatics is well established (26,27). Indeed, we found that by substituting these residues, the observed substrate inhibition was attenuated, and the remaining AbLpxM activity exhibited a V max of ∼0.6·min −1 , directly supporting our model (SI Appendix, Fig.…”
Section: Kinetic Analyses Suggest Ablpxm Possesses Multiple Acp-bindingsupporting
confidence: 72%
“…S4D). That ACP interaction with proteins is primarily driven by electrostatics is well established (26,27). Indeed, we found that by substituting these residues, the observed substrate inhibition was attenuated, and the remaining AbLpxM activity exhibited a V max of ∼0.6·min −1 , directly supporting our model (SI Appendix, Fig.…”
Section: Kinetic Analyses Suggest Ablpxm Possesses Multiple Acp-bindingsupporting
confidence: 72%
“…However, the binding of FITC-RJPXD33⌬6-COOH (36 Ϯ 3.5 M) did not show increased affinity to LpxD as it did to LpxA ( Table 2) and reflects the fact that the role of hydrocarbon ruler in EcLpxD is fulfilled by Met-290 instead of a basic histidine residue as with LpxA (Fig. 7D) (10,35).…”
Section: Peptide (Sequence)mentioning
confidence: 99%
“…The Tyr-4 and Leu-6 side chains of RJPXD33 occupy the O-channel, which is postulated to be the binding site for the ester-linked acyl group of substrate UDP-3-O-acyl-GlcN. The six C-terminal residues of RJPXD33 would potentially extend into a binding groove near the C-terminal ␣-helical domain of EcLpxD, which is not present in EcLpxA and has been identified as the ACP binding domain (35). This would explain the role of the six C-terminal residues with respect to the increased affinity of RJPXD33 for LpxD when compared with LpxA as well as the greater loss in affinity between full-length peptide and the C-terminal ⌬6 peptide for LpxD over LpxA.…”
Section: Peptide (Sequence)mentioning
confidence: 99%
“…S6). We compared the surface features of other ACPs in complexes with cognate enzymes (24)(25)(26)(27)(28)(29) to ACP D (Fig. S6).…”
Section: Significancementioning
confidence: 99%